Congenital aortocaval fistula combined with patent ductus arteriosus in an infant: a case report. (29th October 2022) - Jiao, Xianting; Zhao, Liqing; Wu, Yurong; Chen, Sun
Abstract: Congenital aortocaval fistula (ACF) is a rare cardiac malformation. While it can occur in combination with patent ductus arteriosus (PDA), this has not been reported. In this case, a 1-year-old infant had a heart murmur found in a routine physical examination, and PDA was revealed by transthoracic echocardiography and abdominal ACF was detected by three-dimensional coronary artery computed tomography. Percutaneous interventional therapy, used for ACF and PDA, was performed to occlude the malformation. The patient presented good health without any discomfort at a 1-year follow-up. The percutaneous closure of ACF and PDA with an Amplatzer vascular device can be considered an appropriate option. Abstract : Aortocaval fistula (ACF) is a rare condition that is both observed as an acquired and congenital condition and was first described by Syme in 1831 [1].